Examining Uncertainties in Representations of the Carbon Cycle in Earth System Models. (26th November 2013) - Thomas, R. Quinn; McKinley, Galen A.; Long, Matthew C.
<x xml:space="preserve">Abstract</x> Terrestrial and ocean scientists gathered to pursue intellectual fertilization across the traditional land‐ocean disciplinary split in carbon cycle science. The goal was to examine the processes driving uncertainties in representations of the carbon cycle in Earth System Models (ESMs). Ecosystem processes with land and ocean parallels were explored through talks, posters, and breakout sessions on four themes: disturbance, remineralization/decomposition, individual organisms/trophic interactions, and nutrient limitation. Data‐model synthesis and observational constraints on ESM behavior were a common thread among themes. Key data resources were summarized, and many of these have now been posted at https://climatedataguide.ucar.edu.